Seizure activity after xylazine administration in a horse - SAVVAS (Ι. ΣΑΒΒΑΣ) I. (Journal of the Hellenic Veterinary Medical Society, 2017)
A vicious stallion, schedule for castration, became very stressed during the attempts to place a jugular catheter. Finally, xylazine was injected direcdy from the syringe into the jugular vein and immediately the animal fell down and developed seizures. Acepromazine and fluids were administered to successfully treat the condition. No evidence of haematoma formation was noticed. Xylazine in stressed animals may activate al-adrenoceptors, resulting to central neural system excitement and seizures. Moreover, xylazine may had sensitized the myocardium to endogenous catecholamines, resulting to cardiac arrhythmias, cerebral hypoxia and seizures. Xylazine administration in stressed animals may increase the incidence of adverse reactions.